The description of fast food employees' job involvement - Omar, Muhamad Saufiyudin; Ahmad, Rozila; Mustaffa, Che Su (Global Academic Excellence, 2019)
Employees’ job involvement is crucial in determining the success of an organization. However, studies related to employees’ job involvement in Malaysian fast food restaurants are still limited. Therefore, the purpose of this study is to describe the job involvement of fast food employees of restaurants in Wilayah Persekutuan Kuala Lumpur and Selangor, Malaysia. A quantitative study was conducted, and questionnaires were distributed to 688 fast food employees. Result reveals that most of the fast food employees are moderately involved in their job. This is probably due to the nature of the fast food industry that requires a repetitive job, long working hours, provides low job security, and less competitive work. Additionally, moderate job satisfaction, uncomfortable working environment, and tasks overload are also factoring that are considered to be influencing moderate job involvement in this study. This implies that organizations need to encourage their employees to become more involved in their job in the future to improve employees’ satisfaction and performance.